Karakteristik Gagal Nafas - Mas’a, Hafifah Suci; Wahab, Iswan; Muthalib, Abdul (Universitas Pahlawan Tuanku Tambusai, 2024)
Respiratory failure is a critical condition that requires intensive medical attention and is one of the leading causes of death among adult patients. This condition is characterized by the failure of the respiratory system to exchange oxygen and carbon dioxide effectively, which can lead to serious complications such as congestive heart failure, pneumonia, and organ failure. According to WHO and CDC data, respiratory failure contributes to a significant number of deaths with a fairly high incidence in Indonesia. Respiratory failure is a medical condition characterized by the occurrence of severe and sudden shortness of breath that usually occurs within 12-48 hours after a trigger, such as trauma, sepsis and aspiration (entry of gastric secretions or foreign objects into the lungs) due to decreased oxygen levels in the blood oxygen to enter the blood sufficiently. Respiratory failure can cause complications such as having a higher risk of congestive heart failure, having a high risk of pneumonia and suffering from organ failure. There are several types of respiratory failure that are classified based on the causative factors, namely severe acute lung disease, neuromuscular disorders, adult respiratory distress syndrome (ARDS), infant respiratory distress syndrome, acute chronic lung disease.